2006
DOI: 10.1111/j.1445-2197.2006.03730.x
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte Apoptosis in Response to Dislocation of the Hip in the Rat Model

Abstract: Dislocation of a joint causes chondrocyte apoptosis. There is a progressive increase in the apoptotic index with prolonged dislocation of the rat hip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…18 In case the femoral head was unsalvageable, a hip arthroplasty was performed. Other strategies we used to preserve cartilage was prompt hip reduction, which was proven to lower apoptosis of chondrochytes, 19 concentric acetabular reduction and early hip motion exercises. We believe that those combined strategies lowered our rates of early arthritis to 30% compared to 88% in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…18 In case the femoral head was unsalvageable, a hip arthroplasty was performed. Other strategies we used to preserve cartilage was prompt hip reduction, which was proven to lower apoptosis of chondrochytes, 19 concentric acetabular reduction and early hip motion exercises. We believe that those combined strategies lowered our rates of early arthritis to 30% compared to 88% in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…The mean apoptotic index of the control groups in this study was between 0.04 and 0.12. The femoral head apoptotic index rates in other studies ranged from 0.01 to 0.23 [25][26][27]. D'Lima thought that this was related to the artifacts in the culture and cutting technique of the pathological specimens [26][27][28].…”
Section: Discussionmentioning
confidence: 91%
“…However, Dreinhofer et al [3] showed that even if the hip reduction was achieved within the first 6 hours, AVN developed in the femoral head in the long term. In the animal study conducted by Elliot et al [25], dislocation of the rat hip joint for more than 1 hour caused a significant increase in the apoptotic index. In our study, the apoptotic index significantly increased with the duration of dislocation in both the experimental and the control groups.…”
Section: Discussionmentioning
confidence: 92%
“…15 Furthermore, new laboratory evidence suggests that a prolonged dislocation time will increase in chondrocyte apoptosis, as shown when increasing time to reduction for hip dislocation in a rat model. 16 Similarly, Torzilli et al 17 reported subchondral fractures and decreased metabolic activity in cartilage exposed to a compression injury.…”
Section: E 2f 2h 2gmentioning
confidence: 98%